Movimiento de juristas, circulación del derecho: Republicanos españoles en América - Eva Elizabeth Martínez Chávez (Clio@Themis, 2022)
The objective of this article is to analyze the circulation of law that was generated with the movement of hundreds of Spanish republicans with degrees in law to America at the conclusión of the Civil War (1936-1939). It documents the contributions they made in the countries where they settled, principally Mexico – the nation that received the greatest number – and the paths they had to follow to continue their academic activities. The research is based on hemerographic and bibliographic sources, as well as documents held in historical archives in Spain and the Americas.